AB121. SOH26AB_0230. Mortality in patients over 65 years with proximal humerus fractures: a systematic review of 414,379 shoulders with meta-analysis - O’Dwyer, Liam; Rowsome, Muiris; Davey, Martin; van der Stok, Johan; Leahy, Aoife; Cassidy, John Tristan (Mesentery and Peritoneum, 2026)
Proximal humerus fractures (PHFs) often lead to significant morbidity for patients and are associated with an increased risk of mortality. The aim of this study was to assess the mortality rate in patients over 65 years old with PHFs. Mortality risk was assessed for 30-day/in-hospital, 1-year, and 5-year follow-up and was compared based on treatment type.